PERAN PENGURUS DALAM MEMBENTUK AKHLAK SANTRI TERHADAP KEDISIPLINAN DI PONDOK PESANTREN AL-MUKHTARIYAH MANDE - Habibah, Ainun Sipa (INTIHA: Islamic Education Journal, 2023)
This research was motivated by the existence of students who could be said to have poor morals, especially in terms of disciplinary attitudes. This research focuses on the management role of Santri. This research aims to find out how and to what extent the role of the Al-Mukhtariyah Mande Islamic Boarding School Management in shaping Santri morals toward discipline. Various activities are carried out to shape the morals of students regarding discipline, including recitation activities, example or exemplary activities, habituation activities, and incidental activities. This type of research is a qualitative approach. The method used is a descriptive method. The data collection techniques used are observation, interviews, and documentation. Data analysis techniques are carried out in three stages, namely, data reduction, data presentation, and conclusions. The results of the research show that the administrators of the Al-Mukhtariyah Mande Islamic boarding school play a role in shaping the students' morals towards discipline which is said to be successful. However, not all students can have the same process of forming disciplined morals and the results will not be the same for all students. Some students can easily apply what they have learned in their daily lives, some students must be constantly reminded, paid attention to, and continuously monitored, and some students rebel and challenge.